Endogeniti Produktivitas Pegawai Berdasarkan Profesionalisme, Beban Kerja, dan Iklim Organisasi - Jefirstson R Riwu Kore; Elbert Manafe; Muhammad Wadud; Luis Marnisah (Publikasi Indonesia, 2026)
This study examined the effects of professionalism, workload, and organizational climate on employee productivity at the Secretariat of the Kupang City Regional House of Representatives (DPRD). A quantitative associative-causal research design was employed to test the relationships among the variables. Data were collected through questionnaires, interviews, and documentation from all 97 employees using a saturated sampling technique. Multiple linear regression analysis was applied to examine the partial and simultaneous effects of the independent variables on productivity. The findings revealed that professionalism (β = 0.144; p = 0.008), workload (β = 0.238; p = 0.001), and organizational climate (β = 0.651; p < 0.001) each had a positive and significant effect on employee productivity. Simultaneously, the three variables also significantly influenced productivity (F = 365.582; p < 0.001). The coefficient of determination (R² = 0.922) indicated that 92.2% of the variance in productivity was explained by the three predictors, demonstrating a very strong relationship. Organizational climate emerged as the strongest predictor, highlighting its critical role in enhancing employee performance within the public sector. These findings suggest that managers in regional legislative secretariats and other government institutions should prioritize strengthening organizational climate through effective leadership, trust, open communication, and organizational support while continuously improving employee professionalism and maintaining balanced workload management. Implementing these strategies is expected to enhance productivity, strengthen organizational performance, improve the quality and accountability of public services, and support the achievement of organizational goals in government institutions through sustainable human resource management practices.